PENEGAKAN HUKUM TERHADAP KASUS PERBUATAN MAIN HAKIM SENDIRI (EIGENRICHTING) DI WILAYAH HUKUM KEPOLISIAN SEKTOR CERENTI - Rayon Syaputra; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Every Indonesian citizens were equal before the law even if someone is a perpetrator, so that legislation prohibits any act of vigilantism (eigenrichting) conducted by the public against criminals. The act of vigilantism (eigenrichting) occurs due to lack of disbelief law enforcement community will be added again weak public awareness of the law itself. Acts of vigilantism in our criminal law is not specifically regulated, but the perpetrators could use the existing provisions in the Criminal Code. Therefore it is necessary to conduct law enforcement vigilante (eigenrichting). But law enforcement against acts of vigilantism (eigenrichting) in the Police Sector jurisdiction Cerenti do not maximized.As for the purpose of this research was to determine the factors that cause people to do acts of vigilantism (eigenrichting) in the jurisdiction of the Police Sector Cerenti, then to determine the constraints on law enforcement in cases of acts of vigilantism (eigenrichting) in the jurisdiction of Police Cerenti sector, as well as to know what is being done to overcome the obstacles in law enforcement against acts of vigilantism (eigenrichting) in the jurisdiction of the Police Sector Cerenti.This study is included in the juridical sociological research that is consistent with the fact that life in society. While the nature of this research is descriptive that provides a clear and detailed picture of the problems studied. The data used is primary data obtained directly from the field, as well as secondary data derived from primary legal materials, secondary and tertiary. Means of data collection is done by interviews, questionnaires, and review of the literature. In the analyzes carried out by means of qualitative and deductive method of thinking.The result of this study is that the cause of the community vigilante acts are due to lack of public confidence terhadapa law enforcement officers, and the weak level of awareness of society itself against the law. The constraints faced by law enforcement in cases of vigilante action is due to insufficient numbers of police personnel Cerenti sector, as well as the concerns of the Police Sector Cerenti in implementing the rule of law. The efforts made to overcome such obstacles Polsek- always coordinate with the nearest police station in order to cover the amount of personnel is lacking, as well as motivation memmberikan to the apparatus to be more propesional and are not afraid to carry out their duties.Keywords: Law Enforcement - Eigenrichting - Offence